Sustainability of mechanisation in the nigerian construction industry - Idoro, Godwin Iroroakpo (Journal of Civil Engineering and Management, 2012)
The study evaluates the level of mechanisation and its sustainability, the relationship between mechanisation and its sustainability and between mechanisation and project outcome. To achieve these, a field survey involving a sample of eighty projects was conducted with the aid of questionnaires. Data were collected on the production methods adopted in excavation and concreting, whether or not the use of plant for the operations were sustainable and the initial and actual delivery time and cost of the projects sampled. The data were analysed using ranking, mean, t-test and Spearman correlation test. The study reveals that the levels of mechanisation and sustainability of mechanisation in the two operations are slightly above average. It also reveals that the level of sustainability of mechanisation has significant influence the level of mechanisation while of mechanisation has significant influence on quality standards and productivity. The study concludes that there is a strong need for measures that will improve the level of mechanisation and its sustainability in the industry and recommend the introduction of plant mobilisation fund by clients, incentives on importation of construction plant and an effective and functional lease market for construction plant as some of the measures that will improve mechanised construction. Mechanizacijos tvarumas nigerijos statybų sektoriuje Santrauka. Tyrime vertinamas mechanizacijos lygis ir tvarumas, taip pat ryšys tarp mechanizacijos ir jos tvarumo bei tarp mechanizacijos ir projekto rezultatų. Įvertinti pasirinkta 80 projektų imtis ir atlikta anketinė apklausa. Buvo renkami duomenys apie kasimo ir betono liejimo darbų metodus, apie tai, ar įrangos naudojimas darbams buvo tvarus, taip pat apie pradinį ir realų darbų atlikimo laiką bei imčiai atrinktų projektų kainą. Duomenys analizuoti naudojant rangavimo, vidurkių, t testo metodus ir Spearmano koreliacijos testą. Tyrimas rodo, kad dviejų minėtų darbų atveju mechanizacijos ir mechanizacijos tvarumo lygiai šiek tiek viršija vidurkį. Jis taip pat rodo, kad mechanizacijos tvarumo lygis daro nemažą įtaką mechanizacijos lygiui, o mechanizacija daro reikšmingą įtaką kokybės standartams ir našumui. Tyrime daroma išvada, kad labai reikia priemonių, kurios pagerins sektoriaus mechanizacijos lygį ir tvarumą, bei rekomenduojamos kelios mechanizuotą statybą pagerinsiančios priemonės: klientams įsteigti įrangos mobilizacijos fondą, skatinti statybų įrangos importą ir sukurti efektyvią bei funkcionuojančią statybos įrangos nuomos rinką. Reikšminiai žodžiai: statybų sektorius, mechanizacija, Nigerija, projekto rezultatai ir tvarumas.